PSHT Logo as Manifestation of Pancasila Ideological Values - Ediyono, Suryo - (KOMUNITAS: INTERNATIONAL JOURNAL OF INDONESIAN SOCIETY AND CULTURE, 2016)
This study aims to analyze and describe meanings on the symbols embodied in the martial arts logo school of Setia Hati Terate Brotherhood (PSHT) and its representation towards the ideological values of Pancasila. The study is based on the Ethnosemiotical approach. This analytical method on the cultural texts connects the understanding of reading the symbolic expressions represented in the PSHT logo. The results conclude that the symbolic entities on PSHT logo imply a concordance on the values between the Peircean semiotic perspectives in the form of the organizational principles confirming the ideological state of Pancasila. The result showed that on the symbol of lotus flower buds, half-bloom and bloom refers to the philosophical meaning of âhaving stability and confidence in social skills, therefore, they donât feel awkward and feeling inferiorâ it would seem difficult to find the meaning of connotation and denotation and thus requires further clarification from the public who involve in the Organizations of PSHT. Identification of such symbols indicating the active-enterprising which motivate the instillation on the values of Pancasila, uniting , maintain and strengthening the unity of the nation, the moving spirit of the nation in undertaking the national development and solving the arising problems in the life of the nation.